Catholic Martyrs and Canon Law: Reassessing the Meaning of Hagiographic Texts in Philip II’s Spain - Feola, Vittoria (Religions, 2025)
This essay is about the uses of martyrdom works in Spain and among Elizabethan English Catholics with special reference to their beatification cause by the Dicastery for the Causes of Saints. There are two related points in this essay. First, Spanish martyrdom was more about fighting the Turks than fighting the Protestant English; secondly, hagiographic texts were more about submitting evidence to Rome for classification as a martyr than overthrowing the English government. We need to consider these two issues together if we are to better understand that the story of Spanish Catholic martyrs is really not about a larger narrative of Catholics v. Protestants, especially English Protestants. I argue, first, that late sixteenth-century European works about martyrdom reflected competing definitions of the experience. This diversity cannot be summarised in Protestant vs. Catholic definitions of martyrdom, as has been argued so far. I will show that, within Catholicism, there were two main definitions of martyrdom: first, that which focused on Christian martyrs in relation to other faiths, especially Islam; and, secondly, that which focused on Catholic martyrs in relation to Protestant heretics. I will use Spanish evidence about the former and English and Italian evidence about the latter. Further, I will demonstrate that, within Counterreformation Catholicism, Canon law definitions and beatification procedures impacted the production and uses of martyrdom works both in Spain as well as among English Catholics who were implicated in the Impresa d’Inghilterra during Philip II’s reign. Secondly, I argue that the historiographical debate about whether Elizabethan English Catholics who were tried for treason died for their faith or, indeed, for treason, has been missing the point. I will show, first, that it is reasonable to state they died as martyrs according to Canon law and for treason according to common law; secondly, that most Catholic works about their martyrdom have been wrongly regarded as either hagiographical or aimed at keeping the old faith alive among exiles. New research about the Elizabethan Catholic martyrs conducted in previously ignored Roman archives reveals the importance of martyrdom literature for legal reasons. This essay begins to fill the gap about some of the legal uses of martyrdom literature which the Dicastery for the Causes of Saints needs in order to instruct and rule on beatification causes.